Female clients' gender preferences for frontline health workers who provide maternal, newborn and child health (MNCH) services at primary health care level in Nigeria - Ekechi Okereke; Godwin Unumeri; Akinwumi Akinola; George Eluwa; Sylvia Adebajo (BMC, 2020)
Abstract Background In Nigeria, anecdotes abound that female clients, particularly within northern Nigeria, have gender-based preferences for frontline health workers (FLHWs) who provide healthcare services. This may adversely affect uptake of maternal newborn and child health services, especially at primary healthcare level in Nigeria, where a huge proportion of the Nigerian population and rural community members in particular, access healthcare services. This study explored female clients' gender preferences for frontline health workers who provide maternal, newborn and child healthcare (MNCH) services at primary healthcare level in Nigeria. Methods The study adopted a cross-sectional quantitative design with 256 female clients' exit interviews from selected primary health facilities within two States - Bauchi (northern Nigeria) and Cross-River (southern Nigeria). Data was collected using Personal Digital Assistants and data analysis was done using SPSS software. Descriptive analysis was carried out using percentage frequency distribution tables. Bivariate analysis was also carried out to examine possible relationships between key characteristic variables and the gender preferences of female clients involved in the study. Results Out of 256 women who accessed maternal, newborn and child health services within the sampled health facilities, 44.1% stated preference for female FLHWs, 2.3% preferred male FLHWs while 53.5% were indifferent about the gender of the health worker. However only 26.6% of female clients were attended to by male FLHWs. Bivariate analysis suggests a relationship between a female client's health worker gender preference and her pregnancy status, the specific reason for which a female client visits a primary healthcare facility, a female client's location in Nigeria as well as the gender of the health worker(s) working within the primary healthcare facility which she visits to access maternal, newborn and child health services. Conclusions The study findings suggest that female clients at primary healthcare level in Nigeria possibly have gender preferences for the frontline health workers who provide services to them. There should be sustained advocacy and increased efforts at community engagement to promote the acceptability of healthcare services from male frontline health workers in order to have a significant impact on the uptake of MNCH services, particularly within northern Nigeria.